Antecedents of Customer Loyalty: Study from Digital Transaction of EWallet Apps: Antecedents of Customer Loyalty: Study from Digital Transaction of E-Wallet Apps - Rizan, Mohamad; Rivai, Agung Kresnamurti; Tejanagara, Farah Chalida Hanoum; Rizky, Rianti Dea (Jurnal Manajemen Indonesia, 2024)
The purpose of this study is to explore the effect of service quality and perceived utility on customer loyalty in the digital money business, with particular emphasis on the intervening function of consumer satisfaction. The research method is quantitative, employing survey methodology. The sample for this study was made up of ewallet users who reside in DKI Jakarta and have made at least two online digital transactions with their e-wallet in the last six months. All variables were trustworthy, valid, and met the standards of the investigation. SPSS and Structural Equation Modeling were used to analyze the data (SEM). The data reveals that, first and foremost, service quality and perceived utility affect customer satisfaction positively. Second, customer satisfaction functions as a moderator between service quality, perceived utility, and client loyalty. Third, customer loyalty is linked to service quality and perceived value, but only in a small way. As a result of this finding, consumer satisfaction plays a critical role in fostering loyalty. The conclusion is that in the digital money business, superior quality and utility may impact clients positively but do not always result in loyalty. To accomplish this, digital currency players must place a premium on client pleasure. Keywords— Customer Satisfaction; Perceived Usefulness,Service; Quality; Customer Loyalty